Need and Rationale of the Adult Immunisation in India: A Review - Madhu Gupta; Adarsh Bansal; Aprajita Mehta; Nikita Sharma (Preventive Medicine: Research & Reviews)
A comprehensive literature review of published articles (till October 2023) was done through PubMed, Embase and Google Scholar search engines to delineate the need for adult immunisation, recommended adult vaccines, barriers to adult immunisation, future research areas and way forward in the Indian context. A total of 29,894 articles were screened from PubMed, Embase and Google Scholar. Of these, a full-text review of 53 articles was done. The findings emphasised the need for adult immunisation in India because of the growing vulnerable elderly population with comorbidities, immunosenescence, waning immunity, rising incidence of VPDs leading to higher morbidity and mortality amongst them, rising cost of hospitalisation and the emergence of antimicrobial resistance. The recommended adult vaccines include human papilloma virus vaccine, pneumococcal vaccine, influenza and typhoid vaccine for healthy adults and special population groups, respectively. Challenges include less prioritisation in the National Vaccination Policy, insufficient awareness amongst healthcare providers and vaccine hesitancy.